The authority of everyday objects : a cultural history of West German industrial design - Betts, Paul (University of California Press, 2004)
From the Werkbund to the Bauhaus to Braun, from furniture to automobiles to consumer appliances, twentieth-century industrial design is closely associated with Germany. In this pathbreaking study, Paul Betts brings to light the crucial role that design played in building a progressive West German industrial culture atop the charred remains of the past.
Keywords: Industrial design -- Germany -- History.; Design -- Allemagne -- Histoire.; TECHNOLOGY & ENGINEERING -- Industrial Design -- General.; DESIGN -- Industrial.; ARCHITECTURE -- History -- General.; Industrial design; Germany; Electronic book.; History